Cooperación internacional mexicana en ciencia y tecnología: la relación México-España, puente entre Latinoamérica y el Caribe con Europa - Mier y Terán Casanueva, Luis (Revista Española de Desarrollo y Cooperación, 2023)
Public policies in science, technology and innovation, contribute to the welfare of societies. These policies should include strategies for international cooperation. The collaboration of the Latin American and Caribbean region with Europe is severely limited by structural asymmetries. Mexico and Spain are playing an important role in increasing such collaboration, fostering a more harmonious development of the region.